NIAT PENGGUNAAN APLIKASI E-PATIENT: EFEK INFORMASI MEDIA SOSIAL TERHADAP KEPERCAYAAN - Berlian Yunita Margiati; Didik Setyawan; Finisha Mahaestri Noor (STIE AUB Surakarta, 2019)
This study aims to examine the role of information through social media in the form of information that can encourage individual intention to use e-patient. Establishment of intention to use the e-patient by the trust that was formed from the information quality, perceived value and source credibility. The sampling technique is purposive sampling with a population users of social media RSUD Dr. Moewardi Surakarta counted 200 respondents. Hypothesis testing is done by the analysis of Structural Equation Model (SEM) using AMOS. The results of this study indicate that individual intentions to use e-patient applications as a means of supporting the hospital significantly make information quality to trust, perceived value of trust, source credibility to trust, and trust in the goal of using the e-patient application. These results provide meaning intended to make the intention to use the e-patient application through trust can be given by the quality of information, perceived value, and the source credibility of the e-patient application.